Pattern electroretinogram, blue-yellow visual evoked potentials and the risk of developing visual field defects in glaucoma suspects: a longitudinal “survival” analysis with a very long follow-up - Huchzermeyer, Cord; Lämmer, Robert; Mardin, Christian Y.; Kruse, Friedrich; Kremers, Jan; Horn, Folkert (Graefes Archive For Clinical and Experimental Ophthalmology, 2024)
Purpose: Estimating glaucoma suspects’ risk for visual field defects helps to avoid under- and over-treatment. In this retrospective, longitudinal cohort study with a very long follow-up, we studied whether pattern electroretinograms (PERG) amplitudes and blue-on-yellow visual evoked potential (BY-VEP) latencies can predict visual field defects. Methods: Participants of the Erlangen Glaucoma Study were examined with PERG and BY-VEP between 9/1991 and 8/2001. Stimuli were created using an optical bench with Maxwellian view and consisted of vertical gratings (0,88 cpd) in a 32° field for both PERG and BY-VEP. Patients were treated according to clinical standards and performed standard automated perimetry (SAP) annually. Retrospectively, patients with normal SAP at baseline were selected. Primary endpoint was conversion to perimetric glaucoma. Predictive value was modeled using Kaplan–Meier analyses and a multivariate cox proportional hazards model with the continuous variables PERG amplitude, BY-VEP peak time and SAP square-root of loss variance (sLV) after stratification for Jonas classification of the optic discs. Results: Of 412 patients (288: Jonas 0, 103: I, and 21: II; baseline age: 20–60 years), 65 converted to perimetric glaucoma during follow-up (0.5–23.3 years; median 5.5 years). Optic disc classification was a strong risk factor for conversion (log rank p < 0.0001), and patients with more advanced changes progressed earlier. In the multivariate analysis (log rank p = 0.005), only PERG amplitude remained an independent risk factor after stratification for optic disc morphology (p = 0.021), with a 30% higher risk per μV amplitude decrease. Conclusions: PERG helps to estimate glaucoma suspects’ risk for visual field defects.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Electroretinogram; Glaucoma; Perimetry; Survival analysis; Visually evoked potentials